2018
DOI: 10.1186/s12866-018-1302-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-based identification and whole-genome characterisation of the first pteropine orthoreovirus isolated from monkey faeces in Thailand

Abstract: BackgroundThe pteropine orthoreovirus (PRV) was isolated from monkey (Macaca fascicularis) faecal samples collected from human-inhabited areas in Lopburi Province, Thailand. These samples were initially obtained to survey for the presence of hepatitis E virus (HEV).ResultsTwo virus isolates were retrieved by virus culture of 55 monkey faecal samples. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was successfully used to identify the viruses as the segmented dsRNA orthoreovirus. Phylogenetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…During the preparation of this manuscript, the isolation and characterization of an orthoreovirus from monkey faeces collected in Lopburi Province, Thailand was reported [18]. This supports our original hypothesis that animals other than bats may be susceptible to PRV infection and in turn play a role for crossspecies transmission.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…During the preparation of this manuscript, the isolation and characterization of an orthoreovirus from monkey faeces collected in Lopburi Province, Thailand was reported [18]. This supports our original hypothesis that animals other than bats may be susceptible to PRV infection and in turn play a role for crossspecies transmission.…”
Section: Introductionsupporting
confidence: 79%
“…Finally, the recent report by a group in Thailand on the isolation and characterization of a PRV from monkey faecal samples ruled out contamination of these samples with bat faeces. During analysis of the mitochondrial 12S rRNA gene, bat DNA was not detected in the faecal samples, emphasizing monkeys, especially a long-tailed macaque, as potential reservoirs of zoonotic viruses, such as PRV [18]. We believe that the data obtained from our current study supports the notion that the Thai study represents a first isolation of a PRV replicating in monkeys in this region.…”
Section: Discussionsupporting
confidence: 61%
“…Although the mechanism by which PRV transmits between bat species across the range of the virus remains incompletely known, these studies suggested that co-roosting behavior is a major driver of such transmission. The transmission of PRV between related bat species should occur with relative ease under permissive ecological conditions, given the aforementioned zoonotic potential of PRV and further evidence of infection of wild crab-eating macaques (Macaca fascicularis) in Singapore [3] and Thailand [45]. We anticipate that future surveys of pteropids bats of south Asia, the Middle East, and the Horn of Africa may further expand the range of PRV and fill the gaps in the geographic continuum of genetic distance that we have documented.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PRV may spread by frequent contacts among multiple bat species via long-distance movement although the mechanism of PRV transmission between bat species remains unknown. PRV has also been isolated from crab-eating macaques in Thailand [18], and monkeys might act as an intermediate host for the cross-species transmission of PRV and its greater geographical distribution. It would be of interest to investigate PRV prevalence in wildlife, including in fruit bats and moneys, in African countries.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Serological study of PRV in the Philippines reported that 83% of the tested bats (70/ 84) had neutralizing antibodies to PRV, suggesting that PRV is a common infection in wild bat populations in Southeast Asia [16]. PRVs were also isolated from monkey feces collected in Thailand, raising the hypothesis that other mammals, apart from bats, may also play a role in PRV transmission to humans [18]. Recently, a partial PRV genome was detected in an Angolan soft-furred fruit bat (Lissonycteris angolensis) in Uganda via a metagenomic approach, suggesting the new geographic distribution of PRV outside of Asia and Australia [19].…”
Section: Introductionmentioning
confidence: 99%